Global trends facing up to a changing world - Done, Adrian (Palgrave Macmillan IESE business collection, 2012)
Looks at the bigger picture, and the future trends that are going to affect the global business world over the next few years. The author analyses traditional themes such as technology and sustainability but also takes into consideration the effects of developments in other areas such as health, education and demographics